Answer is in the attachment below.
-1<f(x)<1
Answer: 7
Step-by-step explanation: it just makes sense
The rule of product states that:
So, a product is positive if and only if both factors have the same sign, and is negative if only if the factors have opposite sign.
Here 5 - 4/9
multiply 9 and divide 9 to 5. It gives 45/9.
Hence, above fraction becomes,
45/9 - 4/9 = (45 - 4) / 9 = 41 / 9
Hope it helps.
Add like terms
I'm assuming that you forgot to put the parenthasees at the end
so exg
4x+8x=12x
2x^2+3x^2=5x^2
3x^2+3x^3=3x^2+3x^3
group like tems
6x^3+9x-8+5x-9x^2+7
6x^3-9x^2+14x-1